An IGDT‐stochastic model for low‐carbon economic dispatch of integrated electricity‐natural gas systems considering grid‐enhancing technologies - Talebi, Amir; Agabalaye‐Rahvar, Masoud; Mohammadi‐Ivatloo, Behnam; Zare, Kazem; Anvari‐Moghaddam, Amjad (IET generation, transmission & distribution, 2024)
Utilizing wind power alongside flexible resources such as power‐to‐gas technology, gas‐fuel generator, demand response (DR) program, grid‐enhancing technologies, and carbon capture and storage can help to low carbon operation of integrated electricity‐gas systems (IEGSs). Accordingly, this paper proposes a low‐carbon economic dispatch model for the IEGS, in which gas‐fuel generators, DR, and gas‐fuel generator are considered to realize the economic and environmentally friendly operation of these systems. Also, the flexible AC transmission system device as one of the grid‐enhancing technologies is innovatively included in IEGSs to guarantee that wind power is deliverable entire the electricity system. Besides, power‐to‐gas equipped with hydrogen storage is used to absorb the excess wind power to produce CH4. On the other hand, to capture the inherent flexibility of the gas network, the gas‐storing characteristic of pipelines is shown by line pack modelling. To manage uncertainties associated with wind power and DR program, the proposed model is formulated as an IGDT‐stochastic problem. For efficient computation purposes, the present work follows the mixed‐integer linear programming framework. Different case studies are performed on an integrated test system. Numerical simulation results show that the proposed model leads to reducing the total cost, carbon emissions, and wind curtailment by 29%, 16.4%, and 100%, respectively. It can be seen that the proposed low‐carbon ED model is environmentally friendly and has economic benefits. This paper has presented a low‐carbon economic dispatch model for integrated electricity and gas systems, in which flexibility from the generation side (gas‐fuel generator and carbon capture and storage), network side (grid enhancing technologies and line pack), demand side (demand response program), and storage side (power to gas technology equipped with hydrogen storage) is considered to support the environment‐friendly and low‐cost operation. There is no similar work that considers all the mentioned flexible resources in the low‐carbon operation of integrated electricity and gas systems. The obtained results from case studies show that by employing flexible resources (from generation, network, load and storage sides), total cost, total emission, load shedding, and wind curtailment are decreased by 29%, 16.4%, 100%, and 100% respectively. On the other hand, due to the weather conditions and changes in consumer behaviour, the actual response of consumers in the demand response (DR) program and also the output of WE are uncertain. Unlike the uncertainty of wind which follow probability distribution function (PDF), there is no specified PDF for DR uncertainty. Therefore, for the first time, this paper has used a hybrid IGDT‐stochastic method to handle the uncertainties of DR and wind. IGDT is non‐probabilistic approach which does not require PDF.